(untitled) (Jurnal Online Pertanian Tropik, 2021)
This research was conducted in Aek Nabara Village, Marancar District, South Tapanuli Regency. This study aims to determine the production of sap and palm sugar production based on differences in companion plants. Plant samples were taken from rubber companion plants, salak companion plants, cinnamon companion plants, durian companion plants, and cocoa companion plants. The highest sap production was found in sugar palm plants with durian companion plants, while the lowest sap production was found in sugar palm plants with rubber companion plants. The highest sugar production was found in palm plants with rubber companion plants, while the lowest sugar production was found in sugar palm plants with cinnamon companion plants.